Verbal Training Induces Enhanced Functional Connectivity in Japanese Healthy Elderly Population - Yang, Fan-Pei Gloria; Liu, Tzu-Yu; Liu, Chih-Hsuan; Murakami, Shumei; Nakai, Toshiharu (Frontiers in Human Neuroscience, 2022)
The present study employed fMRI to examine the neural substrates of response to cognitive training in healthy old adults. Twenty Japanese healthy elders participated in a 4-week program and practiced a verbal articulation task on a daily basis. Functional connectivity analysis revealed that in comparison to age- and education-matched controls, elders who received the cognitive training demonstrated increased connectivity in the fronto-temporal regions related with language and memory functions and showed significant correlations between the behavioral change in a linguistic task and connectivity in regions for goal-oriented persistence and lexical processing. The increased hippocampal connectivity was consistent with previous research showing efficacious memory improvement and change in hippocampal functioning. Moreover, the increased intra-network connectivity following cognitive training suggested an improved neural differentiation, in contrast to the inter-network activation pattern typical in the aging brain. The current research not only validated the relationship of functional change in the frontal and temporal lobes to age-associated cognitive decline but also showed promise in turning neural change toward the right direction by cognitive training.